PROGRAMA DE CONTROLE DA TUBERCULOSE: AVALIAÇÃO DO GRAU DE IMPLANTAÇÃO NA ATENÇÃO PRIMÁRIA À SAÚDE - Andrea Panhoti Ribeiro (2021)
Tres Lagoas is a municipality of Mato Grosso do Sul state, Brazil, that had, in 2019, 48,6 cases of tuberculosis (TB) for 100,000 residents, higher than the incidence rates of the state and country. The National Tuberculosis Control Program (NTCP) assigns to primary health care (PHC) the prevention, early diagnosis and treatment of tuberculosis (TB), noticing gaps in TB Control Program (TCP) implementation in PHC. This study aimed evaluate the level of TCP implementation in PHC units (PHCU) of Três Lagoas, headquarter of a health region of Mato Grosso do Sul state. A normative assessment study of implementation type was performed, through a quantitative-qualitative approach. Interviews were carried out with PHCU coordinators and secondary data were collected from records of people with TB and their contacts using an instrument based in a Logical Model and Judgment Matrix, specificaly elaborated to this study, based in NTCP recomendations. For qualitative analysis Bardin's content analysis technique was used and, to quantitative analysis, indicators were created and scored (0-2 points) to support the calculation of the level of TCP Implantation (LI), througt the equation ∑ observed score/ ∑ estimated score x 100. The LI was considered “Implemented” when greater than or equal to 80%, “Partially implemented” between 60-80%, “Incipient” between 30-60% and “Not implemented” below 30%. TCP were considered incipiently implemented in PHCU of the municipality, as well as its components "Early Diagnosis", "Adequate and Timely Treatment" and "Prevention Actions", except for the component "Activities TB/HIV Collaboratives” that was assessed as partially implemented. Aspects related to people of TB (disease denial and use of alcohol and other drugs) and related to health services (resistance and/or lack of training/capacity/sensitization, high health professionals turnover, lack of TB protocols, lack of control/monitoring TB indicators, and deficient registration in surveillance instruments/medical records) were indicated as responsible for the weaknesses found. Mostly difficulties are related to the work process, except the qualification/training/awareness that is related to the structure, but intrinsically linked to process indicators. The facilities related with TCP LI ranged from the practice of activities already provided in PHC, involvement/proactivity of health professionals, nurses autonomy, health education skills and the perception that the PHCU should the reference for TB. Keywords: Health Evaluation. Tuberculosis. Primary Health Care.